2012
DOI: 10.1093/eurjhf/hfr158
|View full text |Cite
|
Sign up to set email alerts
|

The European CRT Survey: 1 year (9–15 months) follow‐up results

Abstract: Aims The European CRT Survey is a joint initiative of the Heart Failure Association (HFA) and the European Heart Rhythm Association (EHRA) of the European Society of Cardiology evaluating the contemporary implantation practice of cardiac resynchronization therapy (CRT) in Europe. Methods and results Patients who had a successful CRT implantation were enrolled from 141 centres in 13 countries between November 2008 and June 2009. Baseline demographics, clinical and implantation data were collected, with a follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 42 publications
(52 reference statements)
8
59
1
3
Order By: Relevance
“…The European CRT Survey was a prospective, multinational, observational study. 20 This study showed that CRT-P was independently associated with higher mortality, as well as atrial fibrillation, and advanced HF, 2 comorbidities excluded in REVERSE. There were trends for improved survival in women and with longer QRS duration, similar to the present study.…”
Section: Discussionmentioning
confidence: 75%
“…The European CRT Survey was a prospective, multinational, observational study. 20 This study showed that CRT-P was independently associated with higher mortality, as well as atrial fibrillation, and advanced HF, 2 comorbidities excluded in REVERSE. There were trends for improved survival in women and with longer QRS duration, similar to the present study.…”
Section: Discussionmentioning
confidence: 75%
“…Begg test showed no evidence of publication bias (P = 0.08) rather than Egger test (P = 0.01), the funnel plot was shown in S1A Fig. A total of 11 studies [8, 1315, 20, 24, 30, 38, 49, 51, 64] reported sex-related differences in relation to heart failure hospitalization or heart failure; the HR for significant heterogeneity, which was calculated using random-effect models, was 0.58 (95% CI, 0.46–0.74, P < 0.0001, Fig 3) (I 2 = 62%; P = 0.003). No evidence of publication bias was found in Begg test (P = 0.76) and Egger test (P = 0.68), and the funnel plot was shown in S1B Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, patients with no ischemic cardiomyopathy (NICM) have been shown to exhibit better outcomes and greater reverse remodeling compared to those with ICM [68]. We further mined the collected data and analyzed the baselines associated with patients exhibiting ischemic causes and found: (1) ischemia is more common in males than in females (83.23% vs. 16.77%) [914, 19, 27, 38, 49], (2) the prevalence of female patients was similar in lower and higher rate ischemic cause subgroups (23.34% vs. 22.82%), (3) Patients with ischemia exhibited a 47% increase in the rate of all-cause mortality (S2 Fig). These findings suggest that male patients have a higher risk of ischemia, which is a certain factor in relation to higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a current report of the European CRT Survey, 6 patients with AF have a poorer 1-year survival than those with sinus rhythm (86% vs. 91%, p = 0.0038). Wilton et al 7 performed a meta-analysis of 23 studies, which have compared the outcomes of CRT patients with (n = 1912) and patients without (n = 5583) AF.…”
Section: Does Af Increase Mortality In Patients With Crt?mentioning
confidence: 83%